Carbon dots crosslinked gel polymer electrolytes for dendrite‐free and long‐cycle lithium metal batteries. Issue 2 (27th May 2022) - Huang, Zun‐Hui; Wei, Ji‐Shi; Song, Tian‐Bing; Ni, Jia‐Wen; Wang, Fei; Xiong, Huan‐Ming
Abstract: Lithium metal batteries (LMBs) with extremely high energy densities have several advantages among energy storage equipment. However, the uncontrolled growth of dendrites and the flammable liquid electrolytes (LEs) often cause safety accidents. All solid‐state batteries seem to be the ultimate choice, but solvent‐free electrolytes usually fail in terms of conductivity at room temperature. Therefore, gel polymer electrolytes (GPEs) with a simple manufacturing process and high ionic conductivity are considered as the most competitive candidates to resolve the present difficulties. Herein, we design a polymeric network structure via esterification and amidation reactions between polyethylene glycol (PEG) and carbon dots (CDs). After incorporation with polyvinylidene fluoride and some LEs, the as‐prepared PEG–CDs composite electrolytes (PCCEs) show a high ionic conductivity of 5.5 mS/cm and an ion transference number of 0.71 at room temperature, as well as good flexibility and thermostability. When the PCCEs are assembled with lithium metal anodes and LiFePO4 or LiCoO2 cathodes, both the cycling stability and the retention rate of these LMBs show excellent performance at room temperature. Abstract : Carbon dots (CDs) and polyethylene glycol (PEG) are connected by chemical reactions to form a PEG–CD network, which is blended with polyvinylidene fluoride and a liquid electrolyte to prepare a novel composite gel electrolyte for lithium metal batteries. Such an electrolyte has good thermal stability, ionic conductivity, and ionic transport number at room temperature. Both LiFePO4 /Li and LiCoO2 /Li batteries with such an electrolyte show excellent cycle stability at room temperature.